Kinetics and mechanism of the silver (I) oxide to silver (II) oxide layer electrooxidation reaction - Salvarezza, Roberto Carlos (1988)
The electroformation of Ag(II) oxide layer during the anodization of silver in 0.1 M NaOH is investigated under potentiostatic and potentiodynamic conditions. Results are discussed in terms of nucleation and growth models and statistical analysis of induction times related to the nucleation kinetics of Ag(II) oxide crystals. The best fitting of results comes out from the application of a progressive nucleation and 3-D growth model under mass transfer control where diffusion of species from the electrode to growing sites is essential for further expansion.